Influence of supplementary feeding and the ram effect on conception rate of Barbarine ewes during spring mating - Lassoued N.; Rekik M.; Ben Salem H. (Nutritional and foraging ecology of sheep and goats, 2009)
A total of 131 Barbarine adult ewes with an average live weight of 37 kg and an initial body condition score (BCS) of 1.25 were used. The ewes were allocated to treatment groups receiving two levels of supplementation during the 3 weeks prior to and the 4 weeks during mating. Ewes in treatment H were given a diet composed of 0.5 kg of hay and 0.5 kg of concentrate per ewe per day providing 130% of the metabolisable energy for maintenance (MEM) while ewes in treatment L remained underfed during this period and received each per day 0.2 kg of hay and 0.2 kg of concentrate representing 70% of the MEM. All the ewes were synchronised using intravaginal progestagen sponges left in situ for 14 days and were introduced to rams at sponges withdrawal. For each feeding regime, approximately half the ewes were artificially inseminated (AI) 24 hours after oestrous manifestation while the remaining ewes were allowed to mate naturally (NM). Ewes that did not hold to artificial insemination were allowed to naturally mate at the return of oestrus. During the first three weeks of application of the feeding regimes, ewes in all treatment groups lost weight and body condition: 36.85 ± 6.45 kg to 32.35 ± 4.64 kg and from 37.4 ± 4.4 kg to 34.4 ± 4.3 kg for the L and H treatments respectively (P < 0.05). BCS diminution reached 0.7 ± 0.57 and 0.59 ± 0.48 for ewes receiving the L and H treatment respectively. Neither the feeding regime nor the method of reproduction had a significant effect on fertility at the induced oestrus (36.4, 40, 30.8 and 31.3% for respectively ewes of the LNM, LAI, HNM and HAI groups). The method of reproduction had no effect on total fertility (51.5, 51.5, 64.7 and 67.7% respectively for ewes of the LNM, LAI, HNM and HAI groups). Levels of litter size were low in comparison to the breed mean values averaging 1.0 ± 0, 1.06 ± 0.24, 1.09 ± 0.29 and 1.09 ± 0.30 for respectively ewes of the LNM, LAI, HNM and HAI groups. It is concluded that for light ewes with a very low body condition that have endured several consecutive dry seasons, supplementary feeding for 3 weeks prior to and 4 weeks during mating coupled to stimulation by rams does not alleviate the negative effect of chronic poor feeding on fertility.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)